Indian rock art of the Southwest - Schaafsma, Polly (University of N.M. Press Albuquerque, New Mexico, 1980)
Presents an illustrated description of carvings and paintings on stone by Native Americans in Utah, Arizona, New Mexico, northern Mexico, and west Texas from 2000 B.C. to the nineteenth century, and explains their interpretations
49676
Keywords: Southwest; Indian art; Petroglyphs; Rock paintings